Implementasi Sistem Aplikasi Pembayaran Digital Payment Dalam Pelaksanaan Pembayaran Berbasis Cashless di Masa Pandemi Covid-19 - Dzakisyah Alyus Mubarak; Muhammad Heru Akhmadi; Erlita Nurma Wati (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2022)
In line with the trend of increasing state expenditure payments, the government uses a digital system to carry out cashless-based payments. The digital system provides advantages in the effectiveness of state expenditure payments to the payee and supports the efficiency of state financial management. One of the digital systems used is the Digital Payment application developed by the Directorate General of Treasury. This study aims to review the use of the Digital Payment application in making non-cash payments to payees (suppliers) in the 2019-2021 period. This study used a qualitative method with literature study techniques and interviews with several informants. The results of this study indicate that the use of Digital Payment in non-cash-based payments is quite effective. Even so, there are still obstacles to the mindset, system flexibility, and human resources so the application has not been implemented optimally. To improve quality, it is necessary to improve the DigiPay application and continuous outreach to MSMEs and work unit treasurers. Keywords: Payment system, Digital Payment, Public Spending, Treasury